SUBSTANSI PENDIDIKAN MULTIKULTURAL PERSPEKTIF GUS DUR - Moch Shohib (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
The plurality of people in Indonesia is one of the icons of Indonesia. With plurality, society is expected to appreciate differences in ethnic groups, races, religions, and cultures. However, the plurality that should be the basis of tolerance of the community, rarely give rise to conflict because of differences. The emergence of conflict is an indicator that Indonesian society is still not fully understand the internal conditions of the multicultural. Gus Dur presence in advancing multicultural education emerged as part of a response to the phenomenon of ethnic, racial, religious, and cultural conflicts that often emerged in the midst of a multicultural society. Gus Dur’s multicultural education concept emphasizes the planting of living respect and tolerant to the diversity that lives in the midst of the plural society and the cultivation of generations not only in science and skilled, but also can live together in society as the successor of the nation. This study used the library research method by reviewing some of Gus Dur books. The results showed that differences in religion, race and culture do not contradict one another and do not become a source of division in society. So that the multicultural Islamic education is very urgent to bring flexibility and openness among each other.